LANDASAN YURIDIS PENDIDIKAN DAN PEMBELAJARAN: ANALISIS KOMPREHENSIF TRANSFORMASI REGULASI DALAM MENJAWAB TANTANGAN AKSESIBILITAS DAN KUALITAS DI ERA DIGITAL - M Arief Rahman; Habib Anwar Al-Anshari (STKIP Subang, 2026)
This paper aims to analyze the juridical basis of the education and learning system in Indonesia, which is currently facing the dynamics of the regulatory transition towards a Golden Indonesia 2045. The main problem in this paper is the legal fragmentation and insynchronization between the constitutional mandate on free education and operational policies on the ground, such as the increase in the cost of higher education and the problems of the zoning system. The importance of writing this assignment lies in the urgency of improving the National Education System Law Plan (RUU Sisdiknas) which is included in the 2025-2026 Prolegnas. The methodology used is normative legal research with legislative, conceptual, and case study approaches through an in-depth review of literature materials. The results found show that although the 20% budget allocation has been met nominally, its effectiveness is hampered by infrastructure disparities, the readiness of educators in the implementation of the Independent Curriculum, and the administrative burden of teachers. These findings underscore the need for a more integrated codification of education law to ensure equitable access for all citizens without discrimination.